Automated battery management system for electric/hybrid electric vehicle. (29th August 2011) - Rao, Gorantla Srinivasa; Rao, G. Kesava; Sivanagaraju, S.; Murthy, G.R.K.; Sudheer, B.C.N.S.
This paper proposes an automated battery management system (ABMS) for electric vehicles (EV) and hybrid electric vehicles (HEV) to increase the lifecycle of the batteries. Automated battery management system is needed to enhance the life of the battery set by individually recharging the batteries and monitoring them while being charged. This will enable the battery management system to recharge the batteries fully and to determine if any of the batteries is not accepting charge. Based on the state of charge (SOC) of the set, a specific number of batteries is automatically selected for propulsion by using computer and associated interfacing circuits. To realise this logic, a programme has been developed in C language which automatically rejuvenates batteries, charges and discharges individual batteries in pack, and protects each battery from over discharge and over charge.